(untitled) (LEARNing Landscapes, 2019)
Rooted in arts-based learning, funds of knowledge, and culturally sustaining pedagogies, this paper describes the experiences of a cohort of preservice teachers who co-created arts integration units with emergent bilingual students, engaging them in the creation of plays based on culturally relevant children’s literature. This cohort was designed by eight professors to prepare professionals to serve the needs of culturally diverse and economically vulnerable communities through arts-based teaching and assessment modalities. We share three telling cases about these preservice teachers’ reflections on their pedagogy and their students’ engagement illustrating how the arts can foster inclusive ways of knowing and communicating.